Two-component polyurethane adhesive

By using two-component thermally conductive polyurethane glue, combining aluminum oxide and benzonitride compound phosphate, the problems of bonding strength and weather resistance of aluminum alloy in electric vehicle battery packs were solved, and the effect of high-strength and V0 level fire protection was achieved.

JP2025510407AActive Publication Date: 2025-04-14DUPONT TECH (SHANGHAI) CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2025501754
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-25
Publication Date
2025-04-14
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide bonding solutions for high strength, weather resistance and fire protection in electric vehicle battery pack applications, especially in the connection of aluminum alloys to other components.

Method used

A two-component thermally conductive polyurethane glue is used, which consists of a polyurethane propolymer made of polyol, polyisocyanate and ammonia silane, and another consists of polyethanol ether polyol and catalyst, which is mixed with at least 20% by weight of aluminum oxide and at least 7% by weight of benzonitride compound phosphate.

Benefits of technology

It realizes high-strength bonding to aluminum alloys (more than 8MPa), and also has V0 fire protection, and maintains good bonding performance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510407000001
    Figure 2025510407000001
  • Figure 2025510407000002
    Figure 2025510407000002
  • Figure 2025510407000003
    Figure 2025510407000003
Patent Text Reader

Abstract

Provided herein are two-component flame retardant polyurethane adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of adhesives, in particular two-component polyurethane adhesives. [Background technology]

[0002] The ongoing drive towards weight reduction has led to an increased use of aluminum alloys in components of vehicle body design, especially in the case of electric vehicles (EVs) where the batteries add to the overall vehicle weight. The batteries themselves also use large amounts of aluminum alloys in various structures and components. For example, the housing of the battery pack is typically made of aluminum, as are the side and edge panels of the battery module. The joining of aluminum alloys to other components in the battery becomes critical. Adhesive bonding is a commonly used joining method for aluminum currently in the automotive industry, along with other joining methods such as welding and riveting. Typical bond strengths required for joining structural components need to be greater than 5 MPa, preferably greater than 10 MPa.

[0003] The most commonly used adhesives for bonding aluminum alloys are based on epoxy and acrylic chemistries. However, epoxy adhesives have a relatively slow cure rate and can be brittle in the cured state. This makes epoxy adhesives difficult to use for structural bonding of aluminum alloys in battery pack applications. Acrylic-based adhesives often have an unpleasant odor and are not very easy to use.

[0004] Polyurethane (PU) adhesives are typically used to bond painted substrates and plastic parts in automotive applications. However, PU adhesives typically do not provide strong and durable bonds to aluminum alloys, and adhesion to aluminum decreases significantly, especially when exposed to harsh weather conditions such as high temperature and humidity. In addition, in battery applications, adhesives used inside the battery pack need to be fire or flame resistant. Flame retardant additives typically used in the polyurethane industry are halogen-containing or phosphorus-based. Unfortunately, these additives often significantly reduce the adhesive or bonding performance of the adhesive, thereby compromising the structural properties of the bonding system. Summary of the Invention [Means for solving the problem]

[0005] In a first aspect, the present invention provides a two-component thermally conductive polyurethane adhesive formulation, the two-component thermally conductive polyurethane adhesive formulation comprising: (A) a first part, (a1) a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; The first part includes: (B) a second part, (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); The second part contains wherein Part A and / or Part B have a D of less than 5 microns such that when Part A and Part B are mixed together (preferably in a 1:1 volume ratio) to form the adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight percent and the melamine polyphosphate concentration is at least 7% by weight. 50 and melamine polyphosphate.

[0006] 1. A method for bonding two or more substrates, comprising the steps of: (1) A two-component thermally conductive polyurethane adhesive formulation comprising: (A) a first part, (a1) a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; The first part includes: (B) a second part, (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); The second part contains wherein Part A and / or Part B comprises aluminum hydroxide having a D50 of less than 5 microns and melamine polyphosphate such that when Part A and Part B are mixed together to form the adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight percent and the melamine polyphosphate concentration is at least 7% by weight; (2) mixing part A with part B to provide an uncured adhesive; (3) applying the uncured adhesive to at least one substrate; (4) placing the uncured adhesive in adhesive contact with a second substrate; (5) A process for curing the uncured adhesive The method includes:

[0007] (1) a first substrate; (2) Second substrate A bonded assembly comprising: a first and a second substrate comprising the following parts A and B: (A) a first part, (a1) a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; The first part includes: (B) a second part, (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); The second part contains and wherein Part A and / or Part B have a D of less than 5 microns such that when Part A and Part B are mixed together to form the adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight and the melamine polyphosphate concentration is at least 7% by weight, and the mixture is cured. 50 and melamine polyphosphate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The inventors have discovered that a flame retardant adhesive can be formulated with polyurethane that: i) has a lap shear strength of greater than 8 MPa on aluminum; ii) has a flame retardant rating of V0; and iii) has good retention of lap shear strength even after prolonged exposure to harsh conditions.

[0009] Definitions and Abbreviations DSC Differential Scanning Calorimetry MDI 4,4'-methylenebis(phenylisocyanate) HDI Hexamethylene Diisocyanate IPDI Isophorone Diisocyanate PU Polyurethane SEC Size Exclusion Chromatography RH Relative Humidity ATH Aluminum trihydroxide MPP Melamine polyphosphate

[0010] The equivalent weight and molecular weight were determined by gel permeation chromatography (GPC) using a Malvern Viscothek GPC max instrument, tetrahydrofuran (THF) was used as the eluent, PL GEL MIXED D (Agilent, 300×7.5 mm, 5 μm) was used as the column, and MALVERN Viscotek TDA (integrated refractive index viscometer and light scattering) was used as the detector.

[0011] The adhesive of the present invention is a two-component polyurethane adhesive comprising part A and part B. Part A and part B may be packaged together as a kit. Part A and part B are mixed in the appropriate ratio, preferably a 1:1 volume ratio, prior to use, and then applied to one or more substrates as soon as possible.

[0012] Parts A and B will now be disclosed in more detail.

[0013] Part A (Isocyanate) Part A comprises a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the prepolymer being partially terminated with silane moieties and having reactive NCO sites.

[0014] The polyisocyanate used to make the prepolymer can be aliphatic, aromatic or a mixture, with aromatic polyisocyanates being preferred. Examples of aromatic polyisocyanates include methylene diphenyl diisocyanate (MDI), polycarbodiimide-modified MDI, toluene diisocyanate (TDI), p-phenylene diisocyanate (PPDI) and naphthalene diisocyanate (NDI). MDI is particularly preferred and / or polycarbodiimide-modified MDI. In some embodiments, a mixture of MDI and polycarbodiimide-modified MDI is used.

[0015] The polyisocyanate used to prepare the prepolymer is preferably used in an amount of 35 to 65% by weight, more preferably 40 to 60% by weight, and particularly preferably 45 to 55% by weight, based on the total weight of component A.

[0016] In a particularly preferred embodiment, the prepolymer is made using 35 to 65 wt. %, more preferably 40 to 60 wt. %, and especially preferably 45 to 55 wt. % MDI and / or polycarbodiimide-modified MDI, based on the total weight of component A.

[0017] The polyol used to make the prepolymer is preferably a polyether polyol. The polyol may have two or more OH groups. Examples of polyether polyols include poly(alkylene oxide) diols, the alkylene groups being C2 to C6, particularly preferably the alkylene groups being C2 to C4. Examples of suitable polyols include poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols. Particularly preferred are poly(propylene oxide) polyols, in particular poly(propylene glycol). In a preferred embodiment, the polyether polyol is a polyether polyol based on propylene glycol. In a particularly preferred embodiment, it is a polyether polyol based on propylene glycol capped with ethylene oxide, with a molecular weight of about 2,000 Da and a functionality of 2.

[0018] The polyether polyol used to prepare the prepolymer is preferably used in an amount of 5 to 20% by weight, more preferably 8 to 15% by weight, and particularly preferably 9 to 12% by weight, based on the total weight of component A.

[0019] In a preferred embodiment, the polyol used to make the prepolymer is a polyether polyol based on propylene glycol, used in an amount of 5 to 20% by weight, more preferably 8 to 15% by weight, particularly preferably 9 to 12% by weight, based on the total weight of component A.

[0020] The polyisocyanate is used in excess relative to the polyether polyol so that the prepolymer is terminated with isocyanate groups. The final prepolymer preferably has an NCO weight percent in the range of 5-30 wt.%, more preferably in the range of 10-25 wt.%.

[0021] The aminosilane of component A preferably has the general formula I or the general formula II:

[0022] [ka]

[0023] (In the formula, R 1 is independently selected from C1-C6 alkyl, and R 2 are independently selected from C2 to C6 alkylene. It is of the following.

[0024] In a preferred embodiment, the aminosilane of component A is of general formula I, R 1 is a C1-C2 alkyl and R2 is a C2-C4 alkylene. In a more preferred embodiment, the aminosilane is of general formula I, where R 1 is methyl and R2 is propylene.

[0025] In another preferred embodiment, the aminosilane of component A is of general formula II, R 1 is a C1-C2 alkyl and R2 is a C2-C4 alkylene. In a more preferred embodiment, the aminosilane is of the general formula II, where R 1 is methyl and R2 is propylene.

[0026] In a particularly preferred embodiment, the aminosilane of component A is bis-(trimethoxysilylpropyl)amine.

[0027] The aminosilane of component A is preferably used in an amount of 0.5 to 4% by weight, more preferably 1 to 3% by weight, and particularly preferably 1.5 to 2.5% by weight, based on the total weight of component A.

[0028] In a preferred embodiment, the aminosilane of component A is bis-(trimethoxysilylpropyl)amine, used in an amount of 0.5 to 4 wt. %, more preferably 1 to 3 wt. %, and particularly preferably 1.5 to 2.5 wt. %, based on the total weight of component A.

[0029] In a preferred embodiment, the prepolymer of component A is made using: 35 to 65% by weight, more preferably 40 to 60% by weight, particularly preferably 45 to 55% by weight, of a polyisocyanate, based on the total weight of component A, from 5 to 20% by weight, more preferably from 8 to 15% by weight, particularly preferably from 9 to 12% by weight, of a polyether polyol, based on the total weight of component A, and 0.5 to 4% by weight, more preferably 1 to 3% by weight, particularly preferably 1.5 to 2.5% by weight, of aminosilane, based on the total weight of component A.

[0030] In a more preferred embodiment, the prepolymer of component A is made using: 35 to 65% by weight, more preferably 40 to 60% by weight, particularly preferably 45 to 55% by weight, of MDI and / or polycarbodiimide-modified MDI or a mixture of MDI and polycarbodiimide-modified MDI, based on the total weight of component A; from 5 to 20% by weight, more preferably from 8 to 15% by weight, particularly preferably from 9 to 12% by weight, of a polyether polyol based on propylene glycol, based on the total weight of component A, preferably a polyether polyol based on propylene glycol having an OH number (mg KOH / g) of 109 to 115, and From 0.5 to 4% by weight, more preferably from 1 to 3% by weight, particularly preferably from 1.5 to 2.5% by weight, based on the total weight of component A, of 1 is C1-C2 alkyl and R2 is C2-C4 alkylene, more preferably R1 is methyl, and R2 is propylene.

[0031] In a particularly preferred embodiment, the prepolymer of component A is made using: 45 to 55% by weight, based on the total weight of component A, of a mixture of MDI and polycarbodiimide-modified MDI; 9 to 12% by weight, based on the total weight of component A, of a polyether polyol based on propylene glycol having an OH number (mg KOH / g) of 109 to 115, and · 0.5 to 4 wt.-%, more preferably 1 to 3 wt.-%, particularly preferably 1.5 to 2.5 wt.-%, of bis-(trimethoxysilylpropyl)amine, based on the total weight of component A.

[0032] The prepolymer is produced by mixing the components, preferably under a dry and / or inert atmosphere, for a time sufficient for substantially all of the OH groups of the polyol and the amino groups of the aminosilane to react with the polyisocyanate. In a preferred embodiment, mixing is carried out for 1 to 2 hours. The ratios are selected such that the prepolymer is terminated with isocyanate groups and partially with silane groups.

[0033] Part B (Polyol) Part B is one or more polyether polyols; one or more catalysts capable of promoting the reaction of the NCO sites of the prepolymer with the polyol of component B; Includes.

[0034] The polyol used in component B is a polyether polyol. The polyol may have two or more OH groups. Examples of polyether polyols include poly(alkylene oxide) diols, the alkylene groups being C2 to C6, particularly preferably the alkylene groups being C2 to C4. Examples of suitable polyols include poly(ethylene oxide) polyols, poly(propylene oxide) polyols, poly(tetramethylene oxide) polyols. Particularly preferred are poly(propylene oxide) polyols.

[0035] In a preferred embodiment, the polyether polyol of component B is a mixture of polyols having a functionality of 2 to 6. In a particularly preferred embodiment, the polyether polyol of component B is a mixture of at least one diol, at least one triol and at least one polyol with a functionality greater than 3.

[0036] In a preferred embodiment, the polyether polyol of Component B is a mixture comprising or consisting of diols, triols and polyols having a nominal functionality of 5-6.

[0037] In a preferred embodiment, the polyether polyol of component B is a mixture of poly(propylene oxide) polyols having a functionality of 2 to 6. In a particularly preferred embodiment, the polyether polyol of component B is a mixture comprising or consisting of at least one poly(propylene oxide) diol, at least one poly(propylene oxide) triol and at least one poly(propylene oxide) polyol of functionality greater than 3.

[0038] In a preferred embodiment, the polyether polyol of Component B is a mixture comprising or consisting of poly(propylene oxide) diols, poly(propylene oxide) triols, and poly(propylene oxide) polyols having a nominal functionality of 5-6.

[0039] In another preferred embodiment, the polyether polyol of component B comprises 46 to 83 wt. % of a polyether triol, 19 to 46 wt. % of a polyether polyol having a functionality greater than 3, and 4 to 15 wt. % of a polyether diol, based on the total weight of the polyether polyol of component B.

[0040] In another preferred embodiment, the polyether polyol of component B comprises 55 to 65 wt. % of a polyether triol, 25 to 35 wt. % of a polyether polyol having a functionality greater than 3, and 5 to 8 wt. % of a polyether diol, based on the total weight of the polyether polyol of component B.

[0041] In another preferred embodiment, the polyether polyol of Component B comprises 46 to 83 wt. % of a poly(propylene oxide) triol, 19 to 46 wt. % of a poly(propylene oxide) polyol having a functionality greater than 3, and 4 to 15 wt. % of a poly(propylene oxide) diol, based on the total weight of the polyether polyol of Component B.

[0042] In another preferred embodiment, the polyether polyol of Component B comprises 55 to 65 wt. % of a poly(propylene oxide) triol, 25 to 35 wt. % of a poly(propylene oxide) polyol having a functionality greater than 3, and 5 to 8 wt. % of a poly(propylene oxide) diol, based on the total weight of the polyether polyol of Component B.

[0043] The total polyether polyol of Component B is preferably present in an amount of from 35 to 70% by weight, more preferably from 40 to 60% by weight, and especially preferably from 50 to 57% by weight, based on the total weight of Component B.

[0044] In a preferred embodiment, component B is present in an amount of 35 to 70% by weight, more preferably 40 to 60% by weight, particularly preferably 50 to 57% by weight, based on the total weight of component B. (1) 46 to 83 weight percent of a polyether triol, 19 to 46 weight percent of a polyether polyol having a functionality greater than 3, and 4 to 15 weight percent of a polyether diol, based on the total weight of the polyether polyols of component B; or (2) 55 to 65% by weight of a polyether triol, 25 to 35% by weight of a polyether polyol having a functionality greater than 3, and 5 to 8% by weight of a polyether diol, based on the total weight of the polyether polyols of component B; or (3) 46 to 83 weight percent of a poly(propylene oxide) triol, 19 to 46 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 4 to 15 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols of component B; or (4) 55 to 65 weight percent of a poly(propylene oxide) triol, 25 to 35 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 5 to 8 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols of component B. The polyether polyols include mixtures of polyether polyols comprising or consisting of:

[0045] Component B may optionally comprise a diol with a molecular weight of less than 200 Da, more preferably less than 150 Da. Examples include propylene glycol and butanediol, with butanediol (e.g. 1,4-butanediol) being particularly preferred.

[0046] When present, the diol having a molecular weight of less than 200 Da is preferably used in an amount of 5 to 12% by weight, more preferably 6 to 10% by weight, and particularly preferably 8 to 9% by weight, based on the total weight of component B.

[0047] In a preferred embodiment, component B comprises 5 to 12 wt. %, more preferably 6 to 10 wt. %, and particularly preferably 8 to 9 wt. % of butanediol (eg, 1,4-butanediol), based on the total weight of component B.

[0048] Component B comprises one or more catalysts capable of promoting the reaction of the NCO sites of the prepolymer of Component A with one or more polyether polyols of Component B.

[0049] The catalyst is preferably selected from Lewis bases and Lewis acids, of which preferred are tertiary amines including diazabicyclo[2.2.2]octane, tris-2,4,6-((dimethylamino)methyl)phenol, DMDEE (2,2'-dimorpholinodiethyl ether), imidazoles such as 4-methylimidazole, triethanolamine, polyethyleneimine, and diazabicyclo[2.2.2]octane is particularly preferred.

[0050] Also suitable are organotin compounds such as dioctyltin dineodecanoate, dibutyltin di(acetate) and di-n-octyltin bis(isooctylmercaptoacetate). Dibutyltin di(acetate) is particularly preferred.

[0051] In a preferred embodiment, the catalyst comprises diazabicyclo[2.2.2]octane and dibutyltin di(acetate).

[0052] The catalyst is used in an amount of preferably 0.05 to 0.5% by weight, more preferably 0.1 to 0.3% by weight, and particularly preferably 0.2% by weight, based on the total weight of component B.

[0053] In a preferred embodiment, the catalyst is a mixture of diazabicyclo[2.2.2]octane and dibutyltin di(acetate), used in an amount of 0.05 to 0.5% by weight, more preferably 0.1 to 0.3% by weight, particularly preferably 0.2% by weight, based on the total weight of component B.

[0054] Aluminum hydroxide and melamine polyphosphate Part A and / or Part B may have a D of less than 5 microns such that when Part A and Part B are mixed together (preferably in a 1:1 volume ratio) to form the adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight and the melamine polyphosphate concentration is at least 7% by weight, both based on the total weight of the mixture. 50 and melamine polyphosphate. Particle size and particle distribution are measured by light scattering using acetone as the suspending medium.

[0055] The aluminum hydroxide concentration in the adhesive mixture is preferably 20-35% by weight, more preferably 22-26% by weight, based on the total weight of the mixture.

[0056] In a preferred embodiment, aluminum hydroxide is present in Component A at 20 to 35 wt. %, more preferably 22 to 26 wt. %, based on the total weight of Component A.

[0057] In another preferred embodiment, the aluminum hydroxide is present in Component B in an amount of 20 to 35 wt. %, more preferably 22 to 26 wt. %, based on the total weight of Component B.

[0058] In a preferred embodiment, aluminum hydroxide is present in both component A and component B.

[0059] In another preferred embodiment, aluminum hydroxide is present in both component A and component B in an amount from 20 to 35% by weight, more preferably from 22 to 26% by weight, based on the total weight of each component.

[0060] In a preferred embodiment, the D of aluminum hydroxide 50 is less than 3 microns, more preferably about 1 micron.

[0061] Preferably, the adhesive mixture obtained from mixing components A and B (preferably in a 1:1 volume ratio) has 20-35% by weight, more preferably 22-26% by weight, of D 200 μm or less, more preferably about 1 μm, based on the total weight of the mixture. 50 The aluminum hydroxide has the formula:

[0062] In a preferred embodiment, component A comprises 20-35 wt. %, more preferably 22-26 wt. %, based on the total weight of component A, of D 50 The aluminum hydroxide has the formula:

[0063] In another preferred embodiment, component B comprises 20-35 wt. %, more preferably 22-26 wt. %, based on the total weight of component B, of D 50 The aluminum hydroxide has the formula:

[0064] In another preferred embodiment, both component A and component B have 20-35 wt. %, more preferably 22-26 wt. %, of a D 50 The aluminum hydroxide has the formula:

[0065] The concentration of melamine polyphosphate in the adhesive mixture is preferably 7 to 15% by weight, more preferably 8 to 12% by weight, and particularly preferably 9 to 11% by weight, based on the total weight of the mixture.

[0066] In a preferred embodiment, the melamine polyphosphate is present in Component A at from 7 to 15 wt. %, more preferably from 8 to 12 wt. %, based on the total weight of Component A.

[0067] In another preferred embodiment, the melamine polyphosphate is present in Component B at 7 to 15 wt. %, more preferably 8 to 12 wt. %, based on the total weight of Component B.

[0068] In a preferred embodiment, melamine polyphosphate is present in both Component A and Component B.

[0069] In another preferred embodiment, melamine polyphosphate is present in both component A and component B at 7 to 15% by weight, more preferably 8 to 12% by weight, based on the total weight of each component.

[0070] Optional components of components A and B Components A and / or B may further comprise other components such as, for example, talc, molecular sieves, silica (especially amorphous silica), carbon black, and the like.

[0071] Application to substrate Part (A) and Part (B) can be mixed and applied to a substrate using known methods, such as a manual application system or an automated method using a pump system using a 20 liter pail or a 200 liter drum or any other suitable container.

[0072] Preferred substrates include aluminum, electrocoated aluminum, electrocoated steel, laser treated aluminum or passivated aluminum.

[0073] Features The cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminum substrate after curing and standing for 7 days at 23°C and 50% relative humidity of 8 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPa or more, when measured according to the method set out in the examples.

[0074] The cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminum substrate of 6 MPa or more, more preferably 9 MPa or more, especially preferably 10 MPa or more, after curing and standing for 7 days at 23°C and 50% relative humidity followed by 7 days of Cataplasma treatment, as measured according to the method set out in the examples.

[0075] The cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminium substrate after curing and standing for 7 days at 23°C and 50% relative humidity, and after 168 hours at 85°C and 85% relative humidity of 8 MPa or more, more preferably 10 MPa or more, especially preferably 11 MPa or more, when measured according to the method set out in the examples.

[0076] The cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminum substrate after curing and standing for 7 days at 23° C. and 50% relative humidity, and after 1,000 hours at 85° C. and 85% relative humidity of 8 MPa or more, more preferably 10 MPa or more, and especially preferably 11 MPa or more, when measured according to the method set out in the examples.

[0077] The cured adhesive composition resulting from mixing components A and B preferably has a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0078] In a preferred embodiment, the cured adhesive composition resulting from mixing components A and B (7 days at 23° C. and 50% relative humidity) has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, especially preferably 10 MPa or more, after curing and standing for 7 days at 23° C. and 50% relative humidity, as measured according to the method shown in the examples, and a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0079] In another preferred embodiment, the cured adhesive (7 days at 23°C and 50% relative humidity) has a lap shear strength on an aluminum substrate after 7 days of Cataplasma treatment of 6 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPA or more, as measured according to the method shown in the examples, and a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

[0080] In another preferred embodiment, the cured adhesive (7 days at 23° C. and 50% relative humidity) has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 10 MPa or more, and especially preferably 11 MPA or more, after 168 hours at 85° C. and 85% relative humidity, as measured according to the method set forth in the examples, and a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0081] In another preferred embodiment, the cured adhesive composition resulting from mixing components A and B (7 days at 23° C. and 50% relative humidity) has a lap shear strength on an aluminum substrate after 1000 hours at 85° C. and 85% relative humidity of 8 MPa or more, more preferably 10 MPa or more, especially preferably 11 MPA or more, and a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0082] Particularly preferred embodiments The following are particularly preferred embodiments of the present invention.

[0083] 1. A two-component thermally conductive polyurethane adhesive formulation comprising: (A) a first part, (a1) a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; The first part includes: (B) a second part, (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); The second part contains wherein Part A and / or Part B have a D of less than 5 microns such that when Part A and Part B are mixed together to form the adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight percent and the melamine polyphosphate concentration is at least 7% by weight.50 and melamine polyphosphate.

[0084] 2. A method for bonding two or more substrates, comprising the steps of: (1) A two-component thermally conductive polyurethane adhesive formulation comprising: (A) a first part, (a1) a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; The first part includes: (B) a second part, (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); The second part contains wherein Part A and / or Part B have a D of less than 5 microns such that when Part A and Part B are mixed together to form the adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight percent and the melamine polyphosphate concentration is at least 7% by weight. 50 and melamine polyphosphate, (2) mixing part A with part B to provide an uncured adhesive; (3) applying the uncured adhesive to at least one substrate; (4) placing the uncured adhesive in adhesive contact with a second substrate; (5) A process for curing the uncured adhesive The method includes:

[0085] 3.(1) a first substrate; (2) Second substrate A bonded assembly comprising: a first and a second substrate comprising the following parts A and B: (A) a first part, (a1) a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO moieties; The first part includes: (B) a second part, (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of the NCO moieties of (a1) with (b1); The second part contains and wherein Part A and / or Part B have a D of less than 5 microns such that when Part A and Part B are mixed together to form the adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight and the melamine polyphosphate concentration is at least 7% by weight, and the mixture is cured. 50 and melamine polyphosphate.

[0086] 4. Any one of the preceding embodiments, wherein the polyisocyanate used to make the prepolymer is aromatic.

[0087] 5. Any one of the preceding embodiments, wherein the polyisocyanate used to make the prepolymer is selected from methylene diphenyl diisocyanate (MDI), polycarbodiimide modified MDI, toluene diisocyanate (TDI), p-phenylene diisocyanate (PPDI), naphthalene diisocyanate (NDI), and mixtures thereof.

[0088] 6. Any one of the preceding embodiments, wherein the polyisocyanate used to make the prepolymer is selected from MDI, polycarbodiimide modified MDI, and mixtures thereof.

[0089] 7. Any one of the preceding embodiments, wherein the polyisocyanate used to make the prepolymer is used in an amount of 35 to 65% by weight, more preferably 40 to 60% by weight, and particularly preferably 45 to 55% by weight, based on the total weight of component A.

[0090] 8. Any one of the preceding embodiments, wherein the prepolymer is made using 35 to 65 wt. %, more preferably 40 to 60 wt. %, and especially preferably 45 to 55 wt. % MDI and / or polycarbodiimide-modified MDI, based on the total weight of component A.

[0091] 9. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer is a polyether polyol.

[0092] 10. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer has two or more OH groups.

[0093] 11. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer is selected from poly(alkylene oxide) diols, the alkylene groups being C2-C6, and particularly preferably the alkylene groups being C2-C4.

[0094] 12. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer is a poly(propylene oxide) polyol.

[0095] 13. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer is a polyether polyol based on propylene glycol capped with ethylene oxide, having a molecular weight of about 2,000 Da, a functionality of 2.

[0096] 14. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer is used in an amount of 5 to 20 wt.%, more preferably 8 to 15 wt.%, and particularly preferably 9 to 12 wt.%, based on the total weight of component A.

[0097] 15. Any one of the preceding embodiments, wherein the polyol used to make the prepolymer is a propylene glycol-based polyether polyol, used at 5 to 20 wt. %, more preferably 8 to 15 wt. %, and especially preferably 9 to 12 wt. %, based on the total weight of component A.

[0098] 16. Any one of the preceding embodiments, wherein the polyisocyanate is used in excess relative to the polyether polyol, such that the prepolymer is terminated with isocyanate groups.

[0099] 17. Any one of the preceding embodiments, wherein the prepolymer is terminated with isocyanate groups having an NCO weight % in the range of 5-30%, preferably in the range of 10-25%.

[0100] 18. The aminosilane of component A is preferably of general formula I or of general formula II:

[0101] [ka]

[0102] (In the formula, R 1 is independently selected from C1-C6 alkyl, and R 2 are independently selected from C2 to C6 alkylene. Any one of the preceding embodiments.

[0103] 19. The aminosilane of component A is of general formula I, R 1 and R2 is C2-C4 alkylene.

[0104] 20. The aminosilane is of the general formula I, R 1 and R2 is propylene.

[0105] 21. The aminosilane of component A is of general formula II, R1 and R2 is C2-C4 alkylene.

[0106] 22. The aminosilane is of the general formula II, R 1 and R2 is propylene.

[0107] 23. Any one of the preceding embodiments, wherein the aminosilane of component A is bis-(trimethoxysilylpropyl)amine.

[0108] 24. Any one of the preceding embodiments, wherein the aminosilane of component A is used in an amount of 0.5 to 4 wt.%, more preferably 1 to 3 wt.%, and particularly preferably 1.5 to 2.5 wt.%, based on the total weight of component A.

[0109] 25. Any one of the preceding embodiments, wherein the aminosilane of component A is bis-(trimethoxysilylpropyl)amine, used at 0.5 to 4 wt.%, more preferably 1 to 3 wt.%, and particularly preferably 1.5 to 2.5 wt.%, based on the total weight of component A.

[0110] 26. The prepolymer of component A is 35 to 65% by weight, more preferably 40 to 60% by weight, particularly preferably 45 to 55% by weight, of a polyisocyanate, based on the total weight of component A, from 5 to 20% by weight, more preferably from 8 to 15% by weight, particularly preferably from 9 to 12% by weight, of a polyether polyol, based on the total weight of component A, and 0.5 to 4% by weight, more preferably 1 to 3% by weight, particularly preferably 1.5 to 2.5% by weight, of aminosilane, based on the total weight of component A Any one of the preceding embodiments, made using.

[0111] 27. The prepolymer of component A is 35 to 65% by weight, more preferably 40 to 60% by weight, particularly preferably 45 to 55% by weight, of MDI and / or polycarbodiimide-modified MDI or a mixture of MDI and polycarbodiimide-modified MDI, based on the total weight of component A; from 5 to 20% by weight, more preferably from 8 to 15% by weight and particularly preferably from 9 to 12% by weight, based on the total weight of component A, of a polyether polyol based on propylene glycol, preferably a polyether polyol based on propylene glycol having an OH number (mg KOH / g) of 109 to 115, and From 0.5 to 4% by weight, more preferably from 1 to 3% by weight, particularly preferably from 1.5 to 2.5% by weight, based on the total weight of component A, of 1 is C1-C2 alkyl and R2 is C2-C4 alkylene, more preferably R 1 R is methyl, and R is propylene Any one of the preceding embodiments, made using.

[0112] 28. The prepolymer of component A is 45 to 55% by weight, based on the total weight of component A, of a mixture of MDI and polycarbodiimide-modified MDI; 9 to 12% by weight, based on the total weight of component A, of a polyether polyol based on propylene glycol having an OH number (mg KOH / g) of 109 to 115, and 0.5 to 4% by weight, more preferably 1 to 3% by weight, particularly preferably 1.5 to 2.5% by weight, of bis-(trimethoxysilylpropyl)amine, based on the total weight of component A Any one of the preceding embodiments, made using.

[0113] 29. Any one of the preceding embodiments, wherein the polyether polyol used in component B is selected from poly(alkylene oxide) diols, wherein the alkylene groups are C2 to C6, and particularly preferably, the alkylene groups are C2 to C4, and mixtures thereof.

[0114] 30. Any one of the preceding embodiments, wherein the polyether polyol used in component B is selected from poly(propylene oxide) polyols, and mixtures thereof.

[0115] 31. Any one of the preceding embodiments, wherein the polyether polyol used in component B is a mixture of polyols having a functionality of 2-6.

[0116] 32. Any one of the preceding embodiments, wherein the polyether polyol used in component B is a mixture of at least one diol, at least one triol, and at least one polyol of functionality greater than 3.

[0117] 33. Any one of the preceding embodiments, wherein the polyether polyol used in component B is a mixture comprising or consisting of diols, triols, and polyols having a nominal functionality of 5-6.

[0118] 34. Any one of the preceding embodiments, wherein the polyether polyol used in component B is a mixture of poly(propylene oxide) polyols having a functionality of 2-6.

[0119] 35. Any one of the preceding embodiments, wherein the polyether polyol used in component B is a mixture comprising or consisting of at least one poly(propylene oxide) diol, at least one poly(propylene oxide) triol, and at least one poly(propylene oxide) polyol of functionality greater than 3.

[0120] 36. Any one of the preceding embodiments, wherein the polyether polyol used in component B is a mixture comprising or consisting of poly(propylene oxide) diol, poly(propylene oxide) triol, and poly(propylene oxide) polyol having a nominal functionality of 5 to 6.

[0121] 37. Any one of the preceding embodiments, wherein the polyether polyol used in component B comprises 46 to 83 wt. % of a polyether triol, 19 to 46 wt. % of a polyether polyol having a functionality greater than 3, and 4 to 15 wt. % of a polyether diol, based on the total weight of the polyether polyols in component B.

[0122] 38. Any one of the preceding embodiments, wherein the polyether polyol used in component B comprises 55-65 wt.% of a polyether triol, 25-35 wt.% of a polyether polyol having a functionality greater than 3, and 5-8 wt.% of a polyether diol, based on the total weight of the polyether polyols in component B.

[0123] 39. Any one of the preceding embodiments, wherein the polyether polyol used in component B comprises 46 to 83 wt. % of a poly(propylene oxide) triol, 19 to 46 wt. % of a poly(propylene oxide) polyol having a functionality greater than 3, and 4 to 15 wt. % of a poly(propylene oxide) diol, based on the total weight of the polyether polyols in component B.

[0124] 40. Any one of the preceding embodiments, wherein the polyether polyol used in component B comprises 55 to 65 wt. % of a poly(propylene oxide) triol, 25 to 35 wt. % of a poly(propylene oxide) polyol having a functionality greater than 3, and 5 to 8 wt. % of a poly(propylene oxide) diol, based on the total weight of the polyether polyols in component B.

[0125] 41. Any one of the preceding embodiments, wherein the polyether polyol used in component B is present in an amount of 35 to 70 wt.%, more preferably 40 to 60 wt.%, and particularly preferably 50 to 57 wt.%, based on the total weight of component B.

[0126] 42. Component B is 35 to 70% by weight, more preferably 40 to 60% by weight, particularly preferably 50 to 57% by weight, based on the total weight of component B; (1) 46 to 83 weight percent of a polyether triol, 19 to 46 weight percent of a polyether polyol having a functionality greater than 3, and 4 to 15 weight percent of a polyether diol, based on the total weight of the polyether polyols of component B; or (2) 55 to 65% by weight of a polyether triol, 25 to 35% by weight of a polyether polyol having a functionality greater than 3, and 5 to 8% by weight of a polyether diol, based on the total weight of the polyether polyols of component B; or (3) 46 to 83 weight percent of a poly(propylene oxide) triol, 19 to 46 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 4 to 15 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols of component B; or (4) 55 to 65 weight percent of a poly(propylene oxide) triol, 25 to 35 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 5 to 8 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols of component B. Any one of the preceding embodiments, comprising a mixture of polyether polyols comprising or consisting of:

[0127] 43. Any one of the preceding embodiments, wherein component B comprises a diol of molecular weight less than 200 Da, more preferably less than 150 Da.

[0128] 44. Any one of the preceding embodiments, wherein component B comprises a diol selected from propylene glycol, butanediol, and mixtures thereof.

[0129] 45. Any one of the preceding embodiments, wherein component B comprises a butanediol (e.g., 1,4-butanediol), which is particularly preferred.

[0130] 46. ​​Any one of the preceding embodiments, wherein component B comprises 5 to 12 wt. %, more preferably 6 to 10 wt. %, and particularly preferably 8 to 9 wt. %, of a diol having a molecular weight of less than 200 Da, based on the total weight of component B.

[0131] 47. Any one of the preceding embodiments, wherein component B comprises 5 to 12 wt. %, more preferably 6 to 10 wt. %, and particularly preferably 8 to 9 wt. % butanediol (e.g., 1,4-butanediol), based on the total weight of component B.

[0132] 48. Any one of the preceding embodiments, wherein the catalyst is selected from a Lewis base and a Lewis acid.

[0133] 49. Any one of the previous embodiments, wherein the catalyst comprises a catalyst selected from diazabicyclo[2.2.2]octane, tris-2,4,6-((dimethylamino)methyl)phenol, DMDEE (2,2'-dimorpholinodiethyl ether), imidazole (such as 4-methylimidazole), triethanolamine, polyethyleneimine, and mixtures thereof.

[0134] 50. Any one of the preceding embodiments, wherein the catalyst comprises diazabicyclo[2.2.2]octane.

[0135] 51. Any one of the preceding embodiments, wherein the catalyst comprises an organotin compound.

[0136] 52. Any one of the preceding embodiments, wherein the catalyst comprises an organotin compound selected from dioctyltin dineodecanoate, dibutyltin di(acetate), di-n-octyltin bis(isooctylmercaptoacetate), and mixtures thereof.

[0137] 53. Any one of the preceding embodiments, wherein the catalyst comprises dibutyltin di(acetate).

[0138] 54. Any one of the previous embodiments, wherein the catalyst comprises diazabicyclo[2.2.2]octane and dibutyltin di(acetate).

[0139] 55. Any one of the preceding embodiments, wherein the catalyst is used in an amount of 0.05 to 0.5 wt.%, more preferably 0.1 to 0.3 wt.%, and particularly preferably 0.2 wt.%, based on the total weight of component B.

[0140] 56. Any one of the preceding embodiments, wherein the catalyst is a mixture of diazabicyclo[2.2.2]octane and dibutyltin di(acetate), used in an amount of 0.05 to 0.5 wt. %, more preferably 0.1 to 0.3 wt. %, and particularly preferably 0.2 wt. %, based on the total weight of component B.

[0141] 57. Any one of the preceding embodiments, wherein the aluminum hydroxide concentration in the adhesive mixture resulting from mixing components A and B (preferably in a 1:1 volume ratio) is 20-35 wt.%, more preferably 22-26 wt.%, based on the total weight of the mixture.

[0142] 58. Any one of the preceding embodiments, wherein aluminum hydroxide is present in Component A at 20-35 wt.%, more preferably 22-26 wt.%, based on the total weight of Component A.

[0143] 59. Any one of the preceding embodiments, wherein aluminum hydroxide is present in Component B at 20-35 wt.%, more preferably 22-26 wt.%, based on the total weight of Component B.

[0144] 60. Any one of the preceding embodiments, wherein aluminum hydroxide is present in both component A and component B.

[0145] 61. Any one of the preceding embodiments, wherein aluminum hydroxide is present in both component A and component B at 20-35% by weight, more preferably 22-26% by weight, based on the total weight of each component.

[0146] 62. Aluminum hydroxide D 50 Any one of the preceding embodiments, wherein the pore size is less than 3 microns, more preferably about 1 micron.

[0147] 63. The adhesive mixture obtained from mixing components A and B (preferably in a 1:1 volume ratio) has 20-35% by weight, more preferably 22-26% by weight, of D 200 μm or less, more preferably about 1 μm, based on the total weight of the mixture. 50 Any one of the preceding embodiments, comprising an aluminum hydroxide having the formula:

[0148] 64. Component A comprises 20-35 wt. %, more preferably 22-26 wt. %, based on the total weight of component A, of D 50 Any one of the preceding embodiments, comprising an aluminum hydroxide having the formula:

[0149] 65. Component B comprises 20-35 wt. %, more preferably 22-26 wt. %, based on the total weight of component B, of D 200 μm or less, more preferably about 1 μm or less. 50 Any one of the preceding embodiments, comprising an aluminum hydroxide having the formula:

[0150] 66. Both component A and component B contain 20-35% by weight, more preferably 22-26% by weight, of D 200 μm or less, more preferably about 1 μm, based on the total weight of each component. 50 Any one of the preceding embodiments, comprising an aluminum hydroxide having the formula:

[0151] 67. Any one of the preceding embodiments, wherein the melamine polyphosphate concentration in the adhesive mixture resulting from mixing components A and B (preferably in a 1:1 volume ratio) is 7 to 15 wt. %, more preferably 8 to 12 wt. %, and particularly preferably 9 to 11 wt. %, based on the total weight of the mixture.

[0152] 68. Any one of the preceding embodiments, wherein the melamine polyphosphate is present in Component A at 7 to 15 wt.%, more preferably 8 to 12 wt.%, based on the total weight of Component A.

[0153] 69. Any one of the preceding embodiments, wherein the melamine polyphosphate is present in Component B at 7 to 15 wt.%, more preferably 8 to 12 wt.%, based on the total weight of Component B.

[0154] 70. Any one of the preceding embodiments, wherein melamine polyphosphate is present in both component A and component B.

[0155] 71. Any one of the preceding embodiments, wherein melamine polyphosphate is present in both component A and component B at 7 to 15 wt%, more preferably 8 to 12 wt%, based on the total weight of each component.

[0156] 72. Any one of the preceding embodiments, wherein the cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPa or more, after curing and standing for 7 days at 23° C. and 50% relative humidity, as measured according to the method set forth in the examples.

[0157] 73. Any one of the preceding embodiments, wherein the cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminum substrate of 6 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPa or more, after curing and standing for 7 days at 23° C. and 50% relative humidity followed by cataplasma treatment for 7 days, as measured according to the method set forth in the examples.

[0158] 74. Any one of the preceding embodiments, wherein the cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminum substrate after curing and standing for 7 days at 23° C. and 50% relative humidity, and after 168 hours at 85° C. and 85% relative humidity, of 8 MPa or more, more preferably 10 MPa or more, and especially preferably 11 MPa or more, when measured according to the method set forth in the examples.

[0159] 75. Any one of the preceding embodiments, wherein the cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminum substrate after curing and standing for 7 days at 23° C. and 50% relative humidity, and after 1,000 hours at 85° C. and 85% relative humidity, of 8 MPa or more, more preferably 10 MPa or more, and especially preferably 11 MPa or more, when measured according to the method set forth in the examples.

[0160] 76. Any one of the preceding embodiments, wherein the cured adhesive composition resulting from mixing components A and B preferably has a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0161] 77. Any one of the preceding embodiments, wherein the cured adhesive composition resulting from mixing components A and B (7 days at 23° C. and 50% relative humidity) has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPa or more, after curing and standing for 7 days at 23° C. and 50% relative humidity, as measured according to the method set forth in the examples, and a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0162] 78. Any one of the preceding embodiments, wherein the cured adhesive (7 days at 23° C. and 50% relative humidity) has a lap shear strength on an aluminum substrate after 7 days of Cataplasma treatment of 6 MPa or more, more preferably 9 MPa or more, and especially preferably 10 MPA or more, as measured according to the method set forth in the examples, and a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0163] 79. Any one of the preceding embodiments, wherein the cured adhesive (7 days at 23° C. and 50% relative humidity) has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 10 MPa or more, and especially preferably 11 MPA or more, after 168 hours at 85° C. and 85% relative humidity, as measured according to the method set forth in the examples, and a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity.

[0164] 80. Any one of the preceding embodiments, wherein the cured adhesive composition resulting from mixing components A and B (7 days at 23° C. and 50% relative humidity) has a lap shear strength on an aluminum substrate of 8 MPa or more, more preferably 10 MPa or more, and especially preferably 11 MPA or more, after 1000 hours at 85° C. and 85% relative humidity, as measured according to the method set forth in the examples, and a UL94 rating of V0 after curing for 7 days at 23° C. and 50% relative humidity. EXAMPLES

[0165] [Table 1]

[0166] [Table 2]

[0167] Formation of Part A (Isocyanate Component) The amounts of MDI, polyether polyol and amino silane (Dynasilan 1124) shown in Table 2 were first placed in a planetary mixer and mixed at room temperature for 2 hours at a mixing speed of 300-1,000 rpm, then the fillers ATH, MPP, talc, carbon black and amorphous silica were charged into the mixture. The fillers were pre-dried in an oven at a temperature of 100-200°C until the moisture content was less than 1,000 ppm. The fillers were mixed at a mixing speed of 1,000-2,000 rpm for 30-60 minutes to form a mixture. The mixture was then charged into cartridges and stored.

[0168] Preparation of Part B (Polyol Component) The amounts of polyol, silane (Dynasilan) and catalyst shown in Table 2 were mixed at 500-1,000 rpm for 5-15 minutes, and then the fillers ATH, MPP, talc, amorphous silica and molecular sieve were charged to the mixture. The fillers were pre-dried in an oven at a temperature of 100-200°C until the moisture content was less than 1,000 ppm. The fillers were mixed at a mixing speed of 1,000-2,000 rpm for 30-60 minutes to form a mixture. The mixture was then charged into a cartridge and stored.

[0169] Use of adhesives Part A and Part B were mixed in a 1:1 volume ratio using a static mixer and dispensed manually or robotically onto the substrate.

[0170] method Flammability Adhesive samples were prepared by mixing Part A and Part B in a 1:1 volume ratio and curing the mixture at 23°C and 50% relative humidity for 7 days. The flammability of the samples was measured according to the UL94 flammability test. If burning stopped within 10 seconds on a vertical specimen, the sample was rated V0, and dripping of particles was allowed as long as it did not cause combustion. The results are reported in Table 2.

[0171] Lap Shear Test The lap shear strength on aluminum alloy 3003 was measured according to DIN EN1465. Aluminum substrates (AA6061 T6 1.92mm MF noPT no lub, 140x25mm, 1.9mm thick, from Novelis) were used. The substrates were cleaned with isopropanol before use. The adhesive was produced by mixing part A and part B in a 1:1 volume ratio and applied to one substrate, followed by bonding to the other substrate within 5 minutes. The thickness was adjusted to 1.0mm and the overlap area was 25mmx25mm. The material was cured and left at rest for 7 days at 23°C and 50% relative humidity before lap shear testing. The lap shear specimens were then mounted on a tensometer and lap shear testing was performed using a pulling speed of 10mm / min. The force deflection curves were observed and the strength at break was reported as the lap shear strength.

[0172] Lap shear tests were performed immediately after curing and after 7 days of Cataplasma exposure (Cataplasma conditions were 70° C. and 100% relative humidity for 7 days followed by a 24 hour heat shock at -30° C.), 168 hours at 85° C. and 85% relative humidity, and 1,000 hours at 85° C. and 85% relative humidity. The results are reported in Table 2.

[0173] [Table 3]

[0174] [Table 4]

[0175] [Table 5]

[0176] Inventive Examples 1-4 all exhibit a UL94 rating of V0 and excellent lap shear strength immediately after curing (≧11 MPa). Comparative Examples 5, 6, and 9 also exhibited unacceptable UL94 ratings and lower lap shear strength immediately after curing (<11 MPa). Comparative Examples 7 and 8 were rated V0 but had significantly lower lap shear strength immediately after curing (<9 MPa).

[0177] Inventive Examples 2 and 3 show excellent retention of lap shear strength after 7 days of Cataplasma treatment and after 168 hours at 85° C. and 85% relative humidity. In contrast, Comparative Examples 5 and 6 show unacceptable loss of lap shear strength after 7 days of Cataplasma treatment, and Comparative Examples 5 and 8 show unacceptable loss of lap shear strength after 168 hours at 85° C. and 85% relative humidity.

Claims

1. 1. A two-component thermally conductive polyurethane adhesive formulation comprising: (A) a first part, (a1) a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO sites; A first part including: (B) a second part, (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of said NCO moieties of (a1) with (b1); The second part includes wherein Part A and / or Part B have a D of less than 5 microns such that when Part A and Part B are mixed together to form the adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight percent and the melamine polyphosphate concentration is at least 7% by weight. 50 and melamine polyphosphate.

2. 1. A method for bonding two or more substrates, comprising the steps of: (1) providing a two-component thermally conductive polyurethane adhesive formulation, the two-component thermally conductive polyurethane adhesive formulation comprising: (A) a first part, (a1) a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO sites; A first part including: (B) a second part, (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of said NCO moieties of (a1) with (b1); The second part includes wherein Part A and / or Part B have a D of less than 5 microns such that when Part A and Part B are mixed together to form the adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight percent and the melamine polyphosphate concentration is at least 7% by weight. 50 and melamine polyphosphate, (2) mixing Part A and Part B to provide an uncured adhesive; (3) applying the uncured adhesive to at least one substrate; (4) bringing the uncured adhesive into adhesive contact with a second substrate; (5) A step of curing the uncured adhesive The method includes:

3. A bonded assembly comprising: (1) a first substrate; (2) Second substrate wherein the first and second substrates comprise the following parts A and B: (A) a first part, (a1) a polyurethane prepolymer made from at least one polyol, at least one polyisocyanate and an aminosilane, the polyurethane prepolymer being partially terminated with silane moieties and having reactive NCO sites; A first part including: (B) a second part, (b1) one or more polyether polyols; (b2) one or more catalysts capable of promoting the reaction of said NCO moieties of (a1) with (b1); The second part includes and wherein Part A and / or Part B have a D of less than 5 microns such that when Part A and Part B are mixed together to form an adhesive mixture, the aluminum hydroxide concentration is at least 20% by weight percent and the melamine polyphosphate concentration is at least 7% by weight percent and the mixture is cured. 50 and melamine polyphosphate.

4. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 3, wherein the polyisocyanate used to make the prepolymer is aromatic.

5. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 4, wherein the polyisocyanate used to make the prepolymer is selected from methylene diphenyl diisocyanate (MDI), polycarbodiimide modified MDI, toluene diisocyanate (TDI), p-phenylene diisocyanate (PPDI), naphthalene diisocyanate (NDI) and mixtures thereof.

6. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 5, wherein the polyisocyanate used to make the prepolymer is selected from MDI, polycarbodiimide modified MDI and mixtures thereof.

7. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 6, wherein the polyisocyanate used to make the prepolymer is used in an amount of 35 to 65 wt.-%, more preferably 40 to 60 wt.-%, particularly preferably 45 to 55 wt.-%, based on the total weight of component A.

8. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 7, wherein the prepolymer is made using 35 to 65 wt.-%, more preferably 40 to 60 wt.-%, especially preferred 45 to 55 wt.-% MDI and / or polycarbodiimide modified MDI, based on the total weight of component A.

9. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 8, wherein the polyol used to make the prepolymer is a polyether polyol.

10. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 9, wherein the polyol used to make the prepolymer has two or more OH groups.

11. The polyol used to make the prepolymer is selected from poly(alkylene oxide) diols, the alkylene group being 2 ~C 6 and particularly preferably, the alkylene group is 2 ~C 4 The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 10,

12. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 11, wherein the polyol used to make the prepolymer is a poly(propylene oxide) polyol.

13. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 12, wherein the polyol used to make the prepolymer is a propylene glycol based polyether polyol having a molecular weight of about 2,000 Da, a functionality of 2, capped with ethylene oxide.

14. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 13, wherein the polyol used to make the prepolymer is used in an amount of 5 to 20 wt.-%, more preferably 8 to 15 wt.-%, especially preferred 9 to 12 wt.-%, based on the total weight of component A.

15. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 14, wherein the polyol used to make the prepolymer is a polyether polyol based on propylene glycol, used at 5 to 20 wt.-%, more preferably 8 to 15 wt.-%, especially preferred 9 to 12 wt.-%, based on the total weight of component A.

16. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 15, wherein the polyisocyanate is used in excess relative to the polyether polyol such that the prepolymer is terminated with isocyanate groups.

17. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 16, wherein said prepolymer is terminated with isocyanate groups with an NCO weight % in the range of 5 to 30%, preferably in the range of 10 to 25%.

18. The aminosilane of component A preferably has the general formula I or the general formula II: 【Chemistry 1】 (In the formula, R 1 is C 1 ~C 6 alkyl, and R 2 is C 2 ~C 6 alkylene). The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 17,

19. The aminosilane of component A is of general formula I, R 1 is C 1 ~C 2 alkyl, and R 2 is C 2 ~C 4 20. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of claim 18, wherein the polyvinyl chloride is an alkylene.

20. The aminosilane is of general formula I, R 1 is methyl, and R 2 20. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of claim 18, wherein is propylene.

21. The aminosilane of component A is of general formula II, R 1 is C 1 ~C 2 alkyl, and R 2 is C 2 ~C 4 20. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of claim 18, wherein the polyvinyl chloride is an alkylene.

22. The aminosilane is of general formula II, R 1 is methyl, and R 2 20. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of claim 18, wherein is propylene.

23. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 22, wherein said aminosilane of component A is bis-(trimethoxysilylpropyl)amine.

24. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein said aminosilane of component A is used in an amount of 0.5 to 4 wt.-%, more preferably 1 to 3 wt.-%, particularly preferably 1.5 to 2.5 wt.-%, based on the total weight of component A.

25. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 24, wherein said aminosilane of component A is bis-(trimethoxysilylpropyl)amine, used in an amount of 0.5 to 4 wt.-%, more preferably 1 to 3 wt.-%, especially preferred 1.5 to 2.5 wt.-%, based on the total weight of component A.

26. The prepolymer of component A is from 35 to 65% by weight, more preferably from 40 to 60% by weight, particularly preferably from 45 to 55% by weight, of a polyisocyanate, based on the total weight of component A, - 5 to 20% by weight, more preferably 8 to 15% by weight, particularly preferably 9 to 12% by weight, of a polyether polyol, based on the total weight of component A, and 0.5 to 4% by weight, more preferably 1 to 3% by weight, particularly preferably 1.5 to 2.5% by weight, of aminosilane, based on the total weight of component A A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 25, made using

27. The prepolymer of component A is 35 to 65% by weight, more preferably 40 to 60% by weight, particularly preferably 45 to 55% by weight, of MDI and / or polycarbodiimide-modified MDI or a mixture of MDI and polycarbodiimide-modified MDI, based on the total weight of component A; - 5 to 20% by weight, more preferably 8 to 15% by weight, particularly preferably 9 to 12% by weight, of a polyether polyol based on propylene glycol, preferably a polyether polyol based on propylene glycol having an OH number (mg KOH / g) of 109 to 115, based on the total weight of component A, and 0.5 to 4% by weight, more preferably 1 to 3% by weight, particularly preferably 1.5 to 2.5% by weight, based on the total weight of component A, of compounds of the general formula II, in which R 1 is C 1 ~C 2 alkyl, and R 2 is C 2 ~C 4 More preferably, R 1 is methyl, and R 2 (wherein is propylene) A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 26 made using

28. The prepolymer of component A is 45-55% by weight, based on the total weight of component A, of a mixture of MDI and polycarbodiimide-modified MDI; - 9 to 12 wt. %, based on the total weight of component A, of a propylene glycol-based polyether polyol having an OH number (mg KOH / g) of 109 to 115, and 0.5 to 4% by weight, more preferably 1 to 3% by weight, and particularly preferably 1.5 to 2.5% by weight, of bis-(trimethoxysilylpropyl)amine, based on the total weight of component A. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 27, made using

29. The polyether polyol used in component B is a poly(alkylene oxide) diol (wherein the alkylene group is 2 ~C 6 and particularly preferably, the alkylene group is 2 ~C 4 29. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 28, wherein the adhesive is selected from:

30. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 29, wherein the polyether polyol used in component B is selected from poly(propylene oxide) polyols and mixtures thereof.

31. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 30, wherein the polyether polyol used in component B is a mixture of polyols having a functionality of 2 to 6.

32. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 31, wherein said polyether polyol used in component B is a mixture of at least one diol, at least one triol and at least one polyol of functionality greater than 3.

33. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 32, wherein the polyether polyol used in component B is a mixture comprising or consisting of diols, triols and polyols with a nominal functionality of 5 to 6.

34. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 33, wherein the polyether polyol used in component B is a mixture of poly(propylene oxide) polyols having a functionality of 2 to 6.

35. 35. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 34, wherein the polyether polyol used in component B is a mixture comprising or consisting of at least one poly(propylene oxide) diol, at least one poly(propylene oxide) triol and at least one poly(propylene oxide) polyol of functionality greater than 3.

36. 36. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 35, wherein the polyether polyol used in component B is a mixture comprising or consisting of poly(propylene oxide) diols, poly(propylene oxide) triols and poly(propylene oxide) polyols with a nominal functionality of 5 to 6.

37. 37. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 36, wherein the polyether polyols used in component B comprise 46 to 83 wt. % of polyether triols, 19 to 46 wt. % of polyether polyols with a functionality greater than 3, 4 to 15 wt. % of polyether diols, based on the total weight of polyether polyols of component B.

38. 38. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 37, wherein the polyether polyols used in component B comprise 55 to 65 wt. % of polyether triol, 25 to 35 wt. % of polyether polyols with a functionality greater than 3, 5 to 8 wt. % of polyether diol, based on the total weight of polyether polyols of component B.

39. 39. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 38, wherein the polyether polyols used in component B comprise 46 to 83 wt. % of poly(propylene oxide) triols, 19 to 46 wt. % of poly(propylene oxide) polyols with a functionality greater than 3, 4 to 15 wt. % of poly(propylene oxide) diols, based on the total weight of the polyether polyols of component B.

40. 40. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 39, wherein the polyether polyol used in component B comprises 55 to 65 wt. % of poly(propylene oxide) triol, 25 to 35 wt. % of poly(propylene oxide) polyol with a functionality greater than 3, 5 to 8 wt. % of poly(propylene oxide) diol, based on the total weight of polyether polyols of component B.

41. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein the polyether polyol used in component B is present in an amount of 35 to 70 wt.-%, more preferably 40 to 60 wt.-%, especially preferred 50 to 57 wt.-%, based on the total weight of component B.

42. Component B comprises 35 to 70 wt. %, more preferably 40 to 60 wt. %, and particularly preferably 50 to 57 wt. %, based on the total weight of component B, of a mixture of polyether polyols, said mixture of polyether polyols comprising: (1) 46 to 83 weight percent of a polyether triol, 19 to 46 weight percent of a polyether polyol having a functionality greater than 3, and 4 to 15 weight percent of a polyether diol, based on the total weight of the polyether polyols of component B; or (2) 55 to 65 weight percent of a polyether triol, 25 to 35 weight percent of a polyether polyol having a functionality greater than 3, and 5 to 8 weight percent of a polyether diol, based on the total weight of the polyether polyols of component B; or (3) 46 to 83 weight percent of a poly(propylene oxide) triol, 19 to 46 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 4 to 15 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols of component B; or (4) 55 to 65 weight percent of a poly(propylene oxide) triol, 25 to 35 weight percent of a poly(propylene oxide) polyol having a functionality greater than 3, and 5 to 8 weight percent of a poly(propylene oxide) diol, based on the total weight of the polyether polyols of component B. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 41, comprising or consisting of:

43. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 42, wherein component B comprises a diol of molecular weight less than 200 Da, more preferably less than 150 Da.

44. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 43, wherein component B comprises a diol selected from propylene glycol, butanediol and mixtures thereof.

45. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 44, wherein component B comprises butanediol, such as 1,4-butanediol, which is particularly preferred.

46. 46. ​​A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein component B comprises 5 to 12 wt.-%, more preferably 6 to 10 wt.-%, especially preferred 8 to 9 wt.-%, of a diol with a molecular weight below 200 Da, based on the total weight of component B.

47. 47. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein component B comprises 5 to 12 wt.-%, more preferably 6 to 10 wt.-%, especially preferred 8 to 9 wt.-% butanediol (e.g. 1,4-butanediol), based on the total weight of component B.

48. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 47, wherein the catalyst is selected from Lewis bases and Lewis acids.

49. 49. The two component thermally conductive polyurethane adhesive formulation, method or bonded assembly of any one of claims 1 to 48, wherein the catalyst comprises a catalyst selected from diazabicyclo[2.2.2]octane, tris-2,4,6-((dimethylamino)methyl)phenol, DMDEE (2,2'-dimorpholinodiethyl ether), imidazoles (such as 4-methylimidazole), triethanolamine, polyethyleneimine and mixtures thereof.

50. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of any one of claims 1 to 49, wherein the catalyst comprises diazabicyclo[2.2.2]octane.

51. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 50, wherein the catalyst comprises an organotin compound.

52. 52. The two component thermally conductive polyurethane adhesive formulation, method or bonded assembly of any one of claims 1 to 51, wherein the catalyst comprises an organotin compound selected from dioctyltin dineodecanoate, dibutyltin di(acetate), di-n-octyltin bis(isooctylmercaptoacetate) and mixtures thereof.

53. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 52, wherein the catalyst comprises dibutyltin di(acetate).

54. 54. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of any one of claims 1 to 53, wherein the catalyst comprises diazabicyclo[2.2.2]octane and dibutyltin di(acetate).

55. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein the catalyst is used in an amount of 0.05 to 0.5 wt.-%, more preferably 0.1 to 0.3 wt.-%, particularly preferably 0.2 wt.-%, based on the total weight of component B.

56. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 55, wherein the catalyst is a mixture of diazabicyclo[2.2.2]octane and dibutyltin di(acetate), used in an amount of 0.05 to 0.5 wt.-%, more preferably 0.1 to 0.3 wt.-%, particularly preferably 0.2 wt.-%, based on the total weight of component B.

57. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein the aluminium hydroxide concentration in the adhesive mixture resulting from mixing components A and B (preferably in a 1:1 volume ratio) is 20-35 wt.-%, more preferably 22-26 wt.-%, based on the total weight of the mixture.

58. 58. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein said aluminium hydroxide is present in component A at 20 to 35 wt.%, more preferably 22 to 26 wt.%, based on the total weight of component A.

59. 59. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein said aluminium hydroxide is present in component B at 20 to 35 wt.%, more preferably 22 to 26 wt.%, based on the total weight of component B.

60. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 59, wherein said aluminum hydroxide is present in both part A and part B.

61. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein the aluminium hydroxide is present in both part A and part B at 20 to 35 wt%, more preferably 22 to 26 wt%, based on the total weight of the respective components.

62. The aluminum hydroxide has a D of less than 3 microns, more preferably about 1 micron. 50 62. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 61, having

63. The adhesive mixture obtained from mixing components A and B (preferably in a 1:1 volume ratio) has 20-35% by weight, more preferably 22-26% by weight, of a D of less than 3 microns, more preferably about 1 micron, based on the total weight of the mixture. 50 63. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of any one of claims 1 to 62, comprising an aluminum hydroxide having the formula:

64. Component A has 20-35 wt. %, more preferably 22-26 wt. %, based on the total weight of Component A, of D 50 64. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of any one of claims 1 to 63, comprising an aluminum hydroxide having the formula:

65. Component B has 20-35 wt. %, more preferably 22-26 wt. %, based on the total weight of Component B, of D of less than 3 microns, more preferably about 1 micron. 50 65. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of any one of claims 1 to 64, comprising an aluminum hydroxide having

66. Both component A and component B have 20-35 wt. %, more preferably 22-26 wt. %, based on the total weight of said respective components, of a D 50 66. The two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly of any one of claims 1 to 65, comprising an aluminum hydroxide having the formula:

67. 67. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein the melamine polyphosphate concentration in the adhesive mixture resulting from mixing components A and B (preferably in a 1:1 volume ratio) is 7 to 15 wt.-%, more preferably 8 to 12 wt.-%, especially preferred 9 to 11 wt.-%, based on the total weight of the mixture.

68. 68. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein the melamine polyphosphate is present in component A at 7 to 15 wt%, more preferably 8 to 12 wt%, based on the total weight of component A.

69. 69. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein the melamine polyphosphate is present in component B at 7 to 15 wt.%, more preferably 8 to 12 wt.%, based on the total weight of component B.

70. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 69, wherein melamine polyphosphate is present in both component A and component B.

71. 71. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of the preceding claims, wherein melamine polyphosphate is present in both component A and component B at 7 to 15 wt%, more preferably 8 to 12 wt%, based on the total weight of said respective components.

72. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 71, wherein the cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminium substrate after curing and standing for 7 days at 23°C and 50% relative humidity of at least 8 MPa, more preferably at least 9 MPa and especially preferably at least 10 MPa, when measured according to the method given in the examples.

73. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 72, wherein the cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminium substrate of at least 6 MPa, more preferably at least 9 MPa, especially preferably at least 10 MPa, after curing and standing for 7 days at 23°C and 50% relative humidity followed by cataplasma treatment for 7 days, when measured according to the method given in the examples.

74. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 73, wherein the cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminium substrate of at least 8 MPa, more preferably at least 10 MPa, especially preferably at least 11 MPa, when measured according to the method given in the examples, after curing and standing for 7 days at 23°C and 50% relative humidity followed by 168 hours at 85°C and 85% relative humidity.

75. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 74, wherein the cured adhesive composition resulting from mixing components A and B preferably has a lap shear strength on an aluminium substrate after curing and standing for 7 days at 23°C and 50% relative humidity followed by 1,000 hours at 85°C and 85% relative humidity of at least 8 MPa, more preferably at least 10 MPa and especially preferably at least 11 MPa, when measured according to the method given in the examples.

76. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 75, wherein the cured adhesive composition resulting from mixing components A and B preferably has a UL 94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

77. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 76, wherein the cured adhesive composition resulting from mixing components A and B (for 7 days at 23°C and 50% relative humidity) has a lap shear strength on an aluminium substrate after curing and standing for 7 days at 23°C and 50% relative humidity of at least 8 MPa, more preferably at least 9 MPa, especially preferably at least 10 MPa, when measured according to the method shown in the examples, and a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

78. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 77, wherein the cured adhesive (7 days at 23°C and 50% relative humidity) has a lap shear strength on an aluminium substrate after 7 days of Cataplasma treatment of at least 6 MPa, more preferably at least 9 MPa, especially preferably at least 10 MPa, when measured according to the method shown in the examples, and a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

79. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 78, wherein the cured adhesive (7 days at 23°C and 50% relative humidity) has a lap shear strength on an aluminium substrate after 168 hours at 85°C and 85% relative humidity of at least 8 MPa, more preferably at least 10 MPa, especially preferably at least 11 MPa, when measured according to the method shown in the examples, and a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

80. A two-component thermally conductive polyurethane adhesive formulation, method or bonded assembly according to any one of claims 1 to 79, wherein the cured adhesive composition resulting from mixing components A and B (7 days at 23°C and 50% relative humidity) has a lap shear strength on an aluminium substrate after 1000 hours at 85°C and 85% relative humidity of at least 8 MPa, more preferably at least 10 MPa, especially preferably at least 11 MPa, when measured according to the method shown in the examples, and a UL94 rating of V0 after curing for 7 days at 23°C and 50% relative humidity.

Citation Information

Patent Citations

  • Polyurethane adhesive used for structural bonding of power battery PACK

    CN109609081A

  • Flame-retardant solvent-free two-component polyurethane structural adhesive and preparation method thereof

    CN110951438A

  • Bi-component polyurethane structural adhesive for bonding power batteries and preparation method thereof

    CN111303820A

  • High-strength flame-retardant adhesive tape and preparation method thereof

    CN113861900A

  • Silane-containing and isocyanate-terminated polyurethane polymer

    JP1983109529A